On the weak solutions of the forward problem in EEG - M. I. Troparevsky; D. Rubio (Journal of Applied Mathematics)
The process underlying the generation of the EEG signals can be described as a set of current sources within the brain. The potential distribution produced by these sources can be measured on the scalp and inside the brain by means of an EEG recorder. There is a well-known mathematical model that relates the electric potential in the head with the intracerebral sources. In this work, we study and prove some properties of the solutions of the model for known sources. In particular, we study the error in the potential, introduced by considering an approximated shape of the head.